ANALISIS KOMBINASI CAMPURAN 3D DRAMIX DAN KAWAT BENDRAT PADA SELF COMPACTING CONCRETE (SCC) - Zahra, Ainaya Maudia; Isneini, Mohd; Irianti, Laksmi; Widyawati, Ratna (Universitas Lampung, 2023)
SCC is fresh concrete that is able to flow through the reinforcement and fill the entire space in the mold without requiring manual compaction or mechanical vibration. SCC has a shortage of weak tensile strength values as in other concrete. So an innovation was made, namely the addition of fiber to the concrete. In this study, using a combination of bendrat wire and 3D Dramix with a length of 6 cm and a diameter of 0.8 mm, the volume fraction of the mixture amounted to 1% and 1.5% with a total of 8 combinations. The compressive strength test object was a cylinder with a diameter of 150 mm and a height of 300 mm totaling 24 pieces and the flexural tensile strength test was a beam with a length of 400 mm, a width of 100 mm, and a height of 100 mm totaling 24 pieces. Tests were conducted at the age of 28 days. From the test results, the highest compressive strength occurred in BSV, namely a combination of 1.25% bendrat wire and 0.25% 3D Dramix with an increase in compressive strength of 15.04% of normal concrete. In the flexural tensile strength test, the maximum increase was obtained in BSV, namely the combination of 1.25% bendrat wire and 0.25% 3D Dramix with a percentage increase of 1206.5% from normal concrete. This shows that the addition of 3D Dramix and bendrat wire increases the compressive strength and flexural strength of SCC. However, the more fiber in SCC causes the workability of the concrete to decrease and the pores in the concrete to increase.